2021
DOI: 10.1039/d1ma00308a
|View full text |Cite
|
Sign up to set email alerts
|

Full-colour solvatochromic fluorescence emitted from a semi-aromatic imide compound based on ESIPT and anion formation

Abstract: A multi-colour solvatochromic fluorophore was developed by substituting a fully organic 3-amino-N-cyclohexyl phthalimide group with a p-toluenesulfonyl (tosyl) group. This compound is essentially colourless in the visible region and exhibits...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In order to be consistent with the experiment, the absorption and fluorescence spectra of 3TsAPI in ACN, acetone, chloroform, toluene, and cyclohexane solvents are theoretically calculated and listed in Table 3 (the experimental values are shown in parentheses [ 52 ] ). In accordance with the order of decreasing polarity of solvents, the absorption peaks of the normal structure of 3TsAPI are 340.8 nm (337.0 nm), 341.0 nm (337.0 nm), 342.2 nm (341.0 nm), 343.0 nm (342.0 nm), and 342.8 nm (341.0 nm), respectively, which is completely in agreement with the experimental data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to be consistent with the experiment, the absorption and fluorescence spectra of 3TsAPI in ACN, acetone, chloroform, toluene, and cyclohexane solvents are theoretically calculated and listed in Table 3 (the experimental values are shown in parentheses [ 52 ] ). In accordance with the order of decreasing polarity of solvents, the absorption peaks of the normal structure of 3TsAPI are 340.8 nm (337.0 nm), 341.0 nm (337.0 nm), 342.2 nm (341.0 nm), 343.0 nm (342.0 nm), and 342.8 nm (341.0 nm), respectively, which is completely in agreement with the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Tabuchi and coworks developed a solvated organic fluorophore, 3‐tosylamino‐ N ‐cyclohexylphthalimide (3TsAPI), by introducing a p ‐toluenesulfonyl (tosyl) group to achieve red fluorescence with high fluorescence intensity and suppress the aggregation caused quenching (ACQ) in solutions. [ 52 ] Due to the strong electron‐absorbing ability and steric hindrance of tosyl group, the proton on the amino group can be transferred to the carbonyl group, forming a nearly perfect N–H···O‐type six‐membered ring hydrogen bonding, which provides us an excellent system for studying the kinetics and thermodynamics of ESIPT reaction. In addition, in order to further investigate the solvent effects of 3TsAPI, we optimize the ground‐state structure of 3TsAPI in five solvents with different polarity, including acetonitrile (ACN, Polarity Parameter: 6.2), acetone (Polarity Parameter: 5.4), chloroform (Polarity Parameter: 4.4), toluene (Polarity Parameter: 2.4), and cyclohexane (Polarity Parameter: 0.1) by using density functional theory (DFT), and optimize the excited‐state structure by using time‐dependent density functional theory (TD‐DFT).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that the fluorescent color can be tuned by changing the substituent of 3-amino-N-cyclohexylphthalimide [45]. The targets of the molecular design for fluorophores in this study are (1) high transparency and colorlessness in the visible region and (2) intense yellowish fluorescence under UV irradiation for mixed white-color emission.…”
Section: Td-dft Calculationmentioning
confidence: 94%
“…In our previous studies [21,45], we reported that ESIPT molecules are sensitive to the surrounding environment and may induce dissociation of the hydrogen atom in the amide group, generating an anionic form. The formation of anions in organic solvents was effectively suppressed with the addition of a small amount of TFA.…”
Section: Optical Properties Of Oddc-tfamentioning
confidence: 99%
See 1 more Smart Citation